1988
DOI: 10.1038/336778a0
|View full text |Cite
|
Sign up to set email alerts
|

A malaria T-cell epitope recognized in association with most mouse and human MHC class II molecules

Abstract: An ideal vaccine should elicit a long lasting immune response against the natural parasite, both at the T- and B-cell level. The immune response should occur in all individuals and be directed against determinants that do not vary in the natural parasite population. A major problem in designing synthetic peptide vaccines is that T cells generally recognize peptide antigens only in association with one or a few of the many variants of major histocompatibility complex (MHC) antigens. During the characterization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
162
2

Year Published

1990
1990
2013
2013

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 355 publications
(173 citation statements)
references
References 23 publications
9
162
2
Order By: Relevance
“…23,24 In addition, immunodominant and promiscuous HLA class II-restricted epitopes have been reported for several pathogens, and their use has been proposed for the design of synthetic vaccines potentially effective in a wide proportion of the general population. [25][26][27][28][29] This approach is complicated in HCV infection by viral variability, because useful T-cell epitopes should also be located within conserved regions of the virus to elicit cross-reactive responses effective against all different HCV strains.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…23,24 In addition, immunodominant and promiscuous HLA class II-restricted epitopes have been reported for several pathogens, and their use has been proposed for the design of synthetic vaccines potentially effective in a wide proportion of the general population. [25][26][27][28][29] This approach is complicated in HCV infection by viral variability, because useful T-cell epitopes should also be located within conserved regions of the virus to elicit cross-reactive responses effective against all different HCV strains.…”
Section: Discussionmentioning
confidence: 99%
“…3). At least 1 T-cell line from each patient recognized the core sequence [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] showing that the epitope contained within this region is immunodominant for all patients studied (Figs. 1B and 3).…”
Section: Fine Specificity Of the T-cell Response To Core Ns3 Ns4 Amentioning
confidence: 99%
“…Several studies have demonstrated that flanking residues are critical for T cell recognition of some, but not all, clones (84)(85)(86). However, these observations are probably due to differences in TCR-VotVB usage, whereas in the present study,…”
mentioning
confidence: 99%
“…H-2 d and H-2 k mice responded with high titres of antibodies, while in H-2 b , H-2 q and H-2 s , the responses were lower or absent [4]. Such immunological unresponsiveness in mice may be partially circumvented by coupling the antigen to protein carriers [5] or by inserting promiscuous T-cell epitopes [6][7][8].…”
Section: Introductionmentioning
confidence: 99%